High And Intermediate-High Risk Pulmonary Embolism Management: A 5-Year Intensive Care Unit Casuistic Review - Mendonça, Inês (2024)
Background and Objectives: The optimal management of high-risk and intermediate-high-risk Pulmonary Embolism (PE) is a matter of ongoing debate. This paper aims to assess the short and long-term clinical outcomes associated with different treatment approaches for high-risk and intermediate-high-risk PE within an Intensive Care Unit (ICU) and identify potential areas for improvement. Methods: We conducted a retrospective analysis of patients admitted to an ICU with high and intermediate-high-risk PE between January 2018 and December 2023. The therapeutic approach and clinical outcomes were evaluated: ICU and 28-days survival, ICU and hospital length of stay, major hemorrhagic complications and direct and indirect signs of pulmonary hypertension (PHT). Demographic, comorbid state and severity at admission data were also collected (sex, age, Charlson Comorbidity and APACHE II scores). Results: 64 patients were included: 32 high-risk PE (including 18 in cardiac arrest) [Groups 1-5] and 32 intermediate-high-risk PE [Group 6a-c]. Treatment approaches varied: Group 1 - High-risk PE treated with systemic thrombolysis (ST) (n=18); Group 2 - High-risk PE treated with Veno-arterial Extracorporeal Membrane Oxygenation (VA-ECMO) plus ST (n=6); Group 3 - High-risk PE treated with VA-ECMO alone (n=5); Group 4 - High-risk PE treated with catheter-direct-therapy (n=1); Group 5 - Heparin only (n=2). Group 1 demonstrated an ICU and 28-day survival of 83.0%, while Groups 2 and 3 exhibited survival rates of 66.67% and 60.0%, respectively. There were 10 major bleeding complications in Group 1 and 2. For intermediate-high-risk PE, heparin alone was used in 90%; ICU and 28-day survival rate was 97%. Three patients exhibited signs of PHT during follow-up. Conclusion: This paper provides insights for the decision-making process involved in managing high and intermedi- ate-high-risk PE drawing from a 5-year retrospective cohort study conducted at an ECMO center and literature review. Fur- ther research is needed to identify the specific subgroup within the intermediate-high-risk PE that would benefit from more advanced treatment modalities for both short and long-term outcomes.